105k views
2 votes
If f(x)= x-6 and g(x)=x2(x+3), find g(x) x f(x)

User Sladomic
by
4.7k points

2 Answers

7 votes

Answer:

x⁴ - 3x³ - 18x²

Explanation:

g(x) × f(x)

(x²(x + 3)) × (x - 6)

Expand brackets.

(x³ + 3x²)(x - 6)

x³(x - 6) + 3x²(x - 6)

x⁴ - 6x³ + 3x³ - 18x²

Combine like terms.

x⁴ - 3x³ - 18x²

User Jar
by
4.7k points
0 votes

Answer:

x^4 -3x^3 - 18x^2

Explanation:

f(x)= x-6

g(x)=x^2(x+3),

g(x) * f(x) = (x-6) * x^2(x+3)

= x^2 ( x-6) ( x+3)

FOIL

= x^2 ( x^2 +3x-6x-18)

Combine like terms

= x^2 ( x^2 -3x-18)

Distribute

= x^4 -3x^3 - 18x^2

User Mike Demidov
by
5.3k points